(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 1998)
Analysis of the internal characters, especially the cardinalia and brachidium, of the brachiopod Comelicania Frech from the Southern Alps, confirmed the attribution of this genus to the Superfam. Athyridoidea Davidson and provided a more complete taxonomic description of the Fam. Comelicaniidae Merla. This family includes two genera which differ in the morphology of their cardinalia, i.e. Gruntallina Waterhouse & Gupta, type-species Gruntallina triangularis (Grunt) from the lower Dorashamian of Transcaucasia and Comelicania, type-species Comelicania megalotis (Stache) from the uppermost Bellerophon Fm. of the Southern Alps. The study of a collection composed of more than a hundred specimens highlighted a broad variability of the morphological characters and a pattern of ontogenetic development which demonstrates that classification at the species level is possible only when using mature specimens. Taxonomic revision at the specific level reduced the eleven species of Comelicania from the Southern Alps, described by previous authors, to: C. megalotis (Stache) and C. haueri (Stache). In addition a new species, C. merlai, which characterises the upper Comelicania beds, is proposed.